Komunikasi Interpersonal Orang Tua dan Anak Perempuan Perokok: Perspektif Fundamental Interpersonal Relations Orientation (FIRO) - Nia Agustina Putri; Nurliah Nurliah; Dony Kristian; Harry Isra Muhammad (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze interpersonal communication between parents and female student smokers in the Communication Studies Program at Mulawarman University using the Fundamental Interpersonal Relations Orientation (FIRO) theory. This study employed a qualitative case study approach involving five female students selected through purposive sampling. Data were collected through in-depth interviews and analyzed using the Miles and Huberman interactive analysis model. The findings indicate that the interpersonal needs of inclusion, control, and affection interact in shaping interpersonal communication between parents and daughters. Participants who felt accepted, were given opportunities to express themselves, and received emotional support from their parents demonstrated greater openness in communication. In contrast, dominant parental control and judgmental responses encouraged participants to conceal their smoking behavior. The study also identified differences between expressed and wanted behaviors, indicating that participants limited self-disclosure while still expecting harmonious relationships with their parents. These findings highlight the importance of fulfilling interpersonal needs when discussing socially stigmatized issues.